2015
DOI: 10.1371/journal.pone.0126982
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Functional Abdominal Pain Disorders: A Meta-Analysis

Abstract: ObjectiveWe aimed to review the literature regarding epidemiology of functional abdominal pain disorders in children and to assess its geographic, gender and age distribution including associated risk factors of developing functional abdominal pain.MethodsThe Cochrane Library, MEDLINE, EMBASE, CINAHL and PsychInfo databases were systematically searched up to February 2014. Study selection criteria included: (1) studies of birth cohort, school based or general population samples (2) containing data concerning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
317
9
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(367 citation statements)
references
References 92 publications
(110 reference statements)
13
317
9
18
Order By: Relevance
“…1 A recent meta-analysis showed that prevalence rates of functional abdominal pain disorder were higher in South America (16.8%) and Asia (16.5%) than in North America (13.4%) and Europe (10.5%). 1 Children with AP-FGID tend to have a lower quality of life compared to healthy children, and AP-FGID can commonly cause absences from school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A recent meta-analysis showed that prevalence rates of functional abdominal pain disorder were higher in South America (16.8%) and Asia (16.5%) than in North America (13.4%) and Europe (10.5%). 1 Children with AP-FGID tend to have a lower quality of life compared to healthy children, and AP-FGID can commonly cause absences from school.…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent meta-analysis showed that prevalence rates of functional abdominal pain disorder were higher in South America (16.8%) and Asia (16.5%) than in North America (13.4%) and Europe (10.5%). 1 Children with AP-FGID tend to have a lower quality of life compared to healthy children, and AP-FGID can commonly cause absences from school. 2,3 AP-FGID is one of the most common gastrointestinal problems seen by pediatric gastroenterologists; however, no medications have been approved to treat this disorder in children.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent meta-analysis, FAP is common in youth, with a worldwide pooled prevalence rate of 13.5% [18]. Many youth with FAP either meet current Rome III criteria for functional Corresponding Author: Uma Rao, M.D., Address: University of Tennessee, CMHSRC, 122 Henson Hall, 1618 West Cumberland Avenue, Knoxville, Phone: (865) FAX: (865) 974-1662, urao@utk.edu.…”
Section: Introductionmentioning
confidence: 99%
“…(15,16) The FGID clinical guidelines, known as the Rome III criteria (17), define IBS as abdominal pain or discomfort occurring at least 3 days per month over the preceding 3 months with at least two of the following associated symptoms: improvement with defecation, change in frequency of stool, or change in form or character of stool. The cause is unknown, although a complex etiology with both neurological and intestinal inputs is likely.…”
mentioning
confidence: 99%